Implementasi Aplikasi GPSKU Pada Kendaraan dalam Pengungkapan Tindak Pidana Curanmor (Studi Pada Sat Reskrim Polres Ciamis): Settings Implementation of the GPSKU Application on Vehicles in the Disclosure of Curanmor Crime (Study at the Ciamis Police Criminal Investigation Unit) - Much Billy Abrianto Putra Yasir (Police Studies Review, 2021)
This research is motivated by the high level of Curanmor crime that occurred in t Ciamis, based on the total Crime that occurred in the last 3 years shows the number of cases of Curanmor resolved is less than the cases of unresolved. This is because the disclosures are still using the old or conventional way, there needs to be innovation by relying on technology, namely GPS Tracker which can be used in the disclosure process in terms of investigation and investigation with tracking techniques or Tracking via GPSKU Application, so to make the disclosure process more effective and efficient. This study aims to describe the process of disclosure of criminal acts Curanmor using the GPSKU Application and the factors that influence the use of the GPSKU application by using research methods used with qualitative approaches and data obtained, namely primary and secondary data with interview, observation and study techniques document. Then the research results will be analyzed with Information Technology Theory, Law Enforcement Theory, Investigative Theory, Concept of Investigation, GPSKU Concept, and Concept of Organizational Resources. How to operate the GPSKU Application can be done via Smartphone and Website. With the GPS Track feature that can find out the presence of vehicle. There is a features that the vehicle can turn off remotely via a Smartphone. In the event of theft of a vehicle that has been installed GPS Tracker in the process of disclosure can be simpler by tracking the vehicle through the Application accurately and shut down the vehicle engine remotely then can be arrested against the perpetrators quickly and efficiently and on target. Providing conclusions that the implementation of the GPSKU Application can assist in the disclosure process by utilizing existing features making the disclosure process effectively and efficiently. Thus every case of Curanmor that occurs can be revealed, and it is expected that Curanmor cases in the Ciamis region will decline, while the suggestions from the results of this research can benefit for the future of the police in collaboration with all functions both Binmas and Sabhara and dealers to introduce and require to use GPS devices Tracker on all vehicles.